Omágua: invenção e trajetória de uma categoria étnica colonial no alto Amazonas: séculos XVI-XVIII - Souza, Rosemeire Oliveira (2014)
The Brazilian indigenous history has currently been the subject of a series of discussions and reinterpretations over which researchers seek to take a fresh look at the Brazilian indigenous universe. The Brazilian Amazon is one of the main focuses of this debate, due to among other factors the population characteristics that have been raised through surveys that allow us to rethink the idea of savagery and barbarism imposed on indigenous populations in general. Using the available documentation reports, essays and manuscripts produced by Spanish officers who were in the area and lived in that region from the16th to the 18th centuries our goal is to contribute to the discussion by analyzing both the Omágua populations who lived in the Upper Amazon area and many formulations raised among European travelers who visited the region at that time. We will demonstrate the elements that are present in the construction of the Omágua category and all the implications present in its setting and population group. Thus, one of the main points of this research is to analyze the European presence in the Amazon and how much the invention of categories of viable indigenous peoples was fundamental to the colonial project